1990
DOI: 10.1111/j.1365-3040.1990.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast movement

Abstract: Abstract. Chloroplasts redistribute and/or reorientate in the cell as a response to the light direction, resulting in patterns typical for light of low or high fluence rate, respectively. Usually, the main photoreceptor pigment is a blue‐UV‐absorbing pigment (‘cryptochrome’), but in a few exceptional cases, the reversible red/far‐red system phytochrome is involved. Detection of light direction is based on light refraction and/or on dichroic orientation of photoreceptor molecules. Membrane effects, intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(100 citation statements)
references
References 76 publications
3
97
0
Order By: Relevance
“…67 (2010) 108 F. Silla et al Thompson et al, 1996). Second, chloroplasts can modify their orientation in response to incident irradiance (Haupt and Scheuerlein, 1990), and seasonal changes in irradiance could affect chlorophyll meter readings, as reported for the natural night-day-night cycle (Hoel and Solhaug, 1998). Accordingly, leaf structural changes that affect absorption, transmission and scattering of light across the leaf could provide different CCI readings even though the chlorophyll content per unit area has not changed.…”
Section: Discussionmentioning
confidence: 99%
“…67 (2010) 108 F. Silla et al Thompson et al, 1996). Second, chloroplasts can modify their orientation in response to incident irradiance (Haupt and Scheuerlein, 1990), and seasonal changes in irradiance could affect chlorophyll meter readings, as reported for the natural night-day-night cycle (Hoel and Solhaug, 1998). Accordingly, leaf structural changes that affect absorption, transmission and scattering of light across the leaf could provide different CCI readings even though the chlorophyll content per unit area has not changed.…”
Section: Discussionmentioning
confidence: 99%
“…and Mesotaenium caldariorum, and a higher plant, Pisum sativum, were tested. Mesotaenium is an unicellular alga that also exhibits a lightdependent chloroplast rotation response (9,12). Spirogyra was selected since it is another member of the order Zygnematales and is closely related to Mougeotia but does not exhibit the chloroplast rotation response.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observations discussed above, it has been suggested that light activation of phytochrome leads to a localized increase in intracellular calcium that activates the actomyosin cytoskeleton that drives chloroplast movement (9). Although this proposal is attractive, detailed biochemical analyses of the targets of calcium regulation and their modulation of the actomyosin cytoskeleton are lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations